Egg Food Challenges are Associated with More Gastrointestinal Reactions - Malika Gupta; Liron D. Grossmann; Jonathan M. Spergel; Antonella Cianferoni (MDPI AG, 2015)
Egg allergy is a common pediatric allergy, and is usually outgrown by elementary school age. There is, therefore, a need to perform an oral food challenge (OFC) to establish the presence of food allergy to egg. In this study, we conducted a retrospective review of 2304 OFCs at a pediatric center and analyzed the severity of reactions during egg OFCs and compared them with other foods. The gastrointestinal system (GI) has been reported as more affected in egg food challenge. This study confirmed that 11% of patients undergoing egg OFC had GI symptoms vs. 7% undergoing food challenges for other foods or compared to milk, peanut and tree nut, individually. However, the involvement of lower respiratory tract was less frequent with egg than observed in peanut and tree nut OFC and similar to observed rate in milk. In conclusion, our study confirmed that OFC to egg causes more GI symptoms and less respiratory symptoms compared to other foods, in particular peanuts and tree nuts. However, 27% of children who failed egg OFC had lower respiratory tract reactions and required the use of epinephrine, similarly to children undergoing milk challenge.